PENGARUH KEPUASAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN ORGANISASI DI UNIT-UNIT PELAYANAN PUBLIK KABUPATEN JEMBER - Elok Rosyidah; Isti Fadah; Diana Sulianti K. Tobing (RELASI : JURNAL EKONOMI, 2018)
This study is purposed to analyze the employee performance of Public Service Units Distric Jember such as Department of Population and Civil Registration, Department of Manpower and Transmigration and National Unity and Politics Agency. Job satisfaction and organizational culture are used as the independent variables in order to analyze it. This study is also used organizational commitment as the intervening variabel to measure how high the effect employee performance levels. The population of this study are all the employees such as government employees and honorary employee. The population numbers are 116 employees. The research used Sensus Methode. The collected data used questioners method by giving questions list directly to the respondents. But after retrieval only 106 quetstionnaires were fully loaded. The analysis data technique in this study operated through the program SEM analysis with software IBM SPSS Analisis of Moment Structure (AMOS). Keywords: Job Satisfaction, Organizational Culture, Organizational Commitment and Employee Performance.